Multiple R2R3-MYB Transcription Factors Involved in the Regulation of Anthocyanin Accumulation in Peach Flower - Zhou, Hui; Peng, Qian; Zhao, Jianbo; Owiti, Albert; Ren, Fei; Liao, Liao; Wang, Lu; Deng, Xianbao; Jiang, Quan; Han, Yuepeng (Frontiers in Plant Science, 2016)
Anthocyanin accumulation is responsible for flower coloration in peach. Here, we report the identification and functional characterization of eight flavonoid-related R2R3-MYB transcription factors, designated PpMYB10.2, PpMYB9, PpMYBPA1, Peace, PpMYB17, PpMYB18, PpMYB19 and PpMYB20, respectively, in peach flower transcriptome. PpMYB10.2 and PpMYB9 are able to activate transcription of anthocyanin biosynthetic genes, whilst PpMYBPA1 and Peace have a strong activation on the promoters of proanthocyanin (PA) biosynthetic genes. PpMYB17-20 show a strong repressive effect on transcription of flavonoid pathway genes such as DFR. These results indicate that anthocyanin accumulation in peach flower is coordinately regulated by a set of R2R3-MYB genes. In addition, PpMYB9 and PpMYB10.2 are closely related but separated into two groups, designated MYB9 and MYB10, respectively. PpMYB9 shows a strong activation on the PpUGT78A2 promoter, but with no effect on the promoter of PpUGT78B (commonly called PpUFGT in previous studies). In contrast, PpMYB10.2 is able to activate the PpUFGT promoter, but not for the PpUGT78A2 promoter. Unlike the MYB10 gene that is universally present in plants, the MYB9 gene is lost in most dicot species. Therefore, the PpMYB9 gene represents a novel group of anthocyanin-related MYB activators, which may have diverged in function from the MYB10 genes. Our study will aid in understanding the complex mechanism regulating floral pigmentation in peach and functional divergence of the R2R3-MYB gene family in plants.